Key considerations and challenges in the application of social‐network research for environmental decision making. Issue 3 (7th February 2020) - Guerrero, A. M.; Barnes, M.; Bodin, Ö.; Chadès, I.; Davis, K. J.; Iftekhar, M. S.; Morgans, C.; Wilson, K. A.
Abstract: Attempts to better understand the social context in which conservation and environmental decisions are made has led to increased interest in human social networks. To improve the use of social‐network analysis in conservation, we reviewed recent studies in the literature in which such methods were applied. In our review, we looked for problems in research design and analysis that limit the utility of network analysis. Nineteen of 55 articles published from January 2016 to June 2019 exhibited at least 1 of the following problems: application of analytical methods inadequate or sensitive to incomplete network data; application of statistical approaches that ignore dependency in the network; or lack of connection between the theoretical base, research question, and choice of analytical techniques. By drawing attention to these specific areas of concern and highlighting research frontiers and challenges, including causality, network dynamics, and new approaches, we responded to calls for increasing the rigorous application of social science in conservation. Abstract : Article Impact Statement : Rigor of social‐network research requires attention to dependency assumptions, theoretical grounding, and methods that respond to data needs. Abstract : Consideraciones y Retos Importantes en la Aplicación de la Investigación por medio de Redes Sociales para la Toma de Decisiones Ambientales Resumen: Los intentos por tener un mejor entendimiento del contexto social en el que se toman las decisiones ambientales y de conservación han derivado en un incremento en el interés por las redes sociales humanas. Para mejorar el uso del análisis de redes sociales en la conservación, buscamos en la literatura los estudios recientes que hayan aplicado dichos métodos y los sometimos a una revisión. En esta revisión, examinamos los problemas en el diseño de la investigación y del análisis que limitan la utilidad del análisis de redes. Diecinueve de los 55 artículos publicados entre enero 2016 y junio 2019 exhibieron al menos uno de los siguientes problemas: aplicación de métodos analíticos inadecuados o sensibles a la información incompleta sobre las redes; aplicación de estrategias estadísticas que ignoran la dependencia en la red; o falta de conexión entre la base teórica, la pregunta de investigación y la selección de técnica analítica. Al llamar la atención hacia estas áreas específicas de interés y resaltar las fronteras y retos de la investigación, incluyendo la causalidad, las dinámicas de redes y las estrategias nuevas, respondimos a la necesidad de incrementar la aplicación rigurosa de las ciencias sociales en la conservación.